Uma sequência didática alternativa : conceitos de eletricidade e o efeito fotoelétrico utilizando simulações computacionais - Baliscei, Marcos Paulo (2016)
One of the difficulties faced in Physics teaching at public high school is to fulfill the programmatic content proposed in the pedagogical planning of this curricular component, given the available timetable. The focus of the contents taught is usually concentrated at Mechanics and little is seen about the Electromagnetic theory, much less on the Photoelectric Effect. Thus, it is necessary to seek new approaches that allow the teaching-learning practice to be effective. In this work, an alternative approach is proposed that is the use of virtual simulators freely available on the "internet", in order to cover topics of Electrodynamics and the Photoelectric Effect. The advantage of this proposal is to work around the lack of time and equipment for experimental classes and provide the students, besides the content, better focused classes. The educational product generated is a handout that has been elaborated directed to the students of the Education of Young and Adults (EJA), modality of education whose target audience are people who did not finish the studies at the appropriate age and that presents singular characteristics compared to the regular education. It was implemented in two classes of different categories. For the learning verification a questionnaire was applied before and after the use of the Educational Product, whose answers were analyzed based on David Ausubel's theory of significant learning and Paulo Freire's pedagogy. Indicatives of significant learning was observed, with conceptual evolution in the students' answers that, before the application of the educational product, answered with the knowledge acquired in the daily life, and after the application of the product they were able to answer using scientific knowledge. It was also observed in a positive way an affective learning, which manifestation always follow the significant learning, with the students being interested and excited when exploring a didactic tool different from the ones that they were used to.